2014
DOI: 10.1016/j.bbcan.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the STAT3 signaling pathway in cancer: Role of synthetic and natural inhibitors

Abstract: Signal transducers and activators of transcription (STATs) comprise a family of cytoplasmic transcription factors that mediate intracellular signaling that is usually generated at cell surface receptors and thereby transmit it to the nucleus. Numerous studies have demonstrated constitutive activation of STAT3 in a wide variety of human tumors, including hematological malignancies (leukemias, lymphomas, and multiple myeloma) as well as diverse solid tumors (such as head and neck, breast, lung, gastric, hepatoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
528
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(538 citation statements)
references
References 284 publications
(315 reference statements)
5
528
0
5
Order By: Relevance
“…A previous study indicated a phosphatase-stable phosphopeptide mimics target to the SH2 domain of STAT3 may inhibit the phosphorylation of STAT3 Tyr705 in cultured tumor cells (25). Drugs that control the activation of STAT3 signaling pathway, particularly in their phosphorylated state, are required for gene expression (26). In the present study, Nm23-H1, a metastasis suppressor gene, which inhibits the phosphorylation of STAT3 on Tyr705 via its Ser44 phosphorylation, provides a novel antitumor metastasis strategy in lung cancer A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated a phosphatase-stable phosphopeptide mimics target to the SH2 domain of STAT3 may inhibit the phosphorylation of STAT3 Tyr705 in cultured tumor cells (25). Drugs that control the activation of STAT3 signaling pathway, particularly in their phosphorylated state, are required for gene expression (26). In the present study, Nm23-H1, a metastasis suppressor gene, which inhibits the phosphorylation of STAT3 on Tyr705 via its Ser44 phosphorylation, provides a novel antitumor metastasis strategy in lung cancer A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a known activator of several anti-apoptotic and cell cycle progressive genes. 22 In animal models, STAT3 is a critical factor for promoting myeloid-mediated tumorigenesis. 30 Others have Exosomes isolated from two PC patient plasma samples (PC1 and PC2 Exo) and PANC-1 Exo were co-incubated with monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…STAT signaling has also been implicated in the generation and proliferation of myeloid cells. 22 We therefore tested whether PC-Exo could activate this pathway by checking the phosphorylation status of STAT1 and STAT3. Through western blotting, we showed that both pSTAT1 and pSTAT3 levels were increased in the presence of both PANC-1 exosomes and exosomes isolated from PCpatient plasma.…”
Section: Pc-exo Contribute To Converting Monocytes Into Immunosuppresmentioning
confidence: 99%
“…STAT proteins comprise a family of cytoplasm transcription factors that mediate intracellular signaling triggered by many molecules and thereby transmit it to nucleus. Among STAT proteins, STAT3 intermediates extracellular signals stimulated by cytokines, mainly IL-6, growth factors and other molecules (70). Briefly, the receptor tyrosine kinase Janus kinases (JAK) recruit STAT3, which dimerizes and is translocated to the nucleus where it recognizes specific DNA sequences and activates the transcription of target genes.…”
Section: Nf-ĸb Signal Transduction Pathway and Bcscsmentioning
confidence: 99%